Factors (Benefits, Trust, Self-Efficacy, Ease of Use, Security) Affecting Consumer's Perception on E-Money in Indonesia - Dinna Fatmy Pratiwi; Citra Kusuma Dewi (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
This research based on the developments of technology on payment system which replaced the use of cash as a medium of exchange into the non-cash system. The use of e-money as a non-cash system was made to actualize less cash society by the increase of the use of instrument and non-cash channel. However, the government had made a rule by required various costs to use e-money. As the used of e-money seemed forced by a rule, therefore, costumers might have a bad perception toward it. Hence, this research made to know the factors that affected costumers' perception toward e-money in Indonesia. The method used in this research was quantitative method with type of descriptive and causal research. The variables used in this research are benefits (X1), trust (X2), self-efficacy (X3), ease of use (X4), security (X5), and consumers' perception (Y). The samples are 400 respondents and using the technique of non-probability sampling which covered purposive sampling and snowball sampling. The data analysis was using multiple linear regressions. The research showed that the factor of self-efficacy and security in partial didn't significantly affect the consumers' perception toward e-money in Indonesia, while the factors that significantly affected partially are factors of benefits, ease of use, and trust. However, simultaneously, all factors of Benefits (X1), Trust (X2), Self-efficacy (X3), Ease of Use (X4), and Security (X5) significantly affected consumers' perception (Y) toward e-money in Indonesia.